Transformation in cities and regions: Current themes in Germany and France - Three significant points of discussion - Evelyn Gustedt; Ulrike Grabski-Kieron; Christophe Demazière; Didier Paris (Cities and metropolises in France and Germany, 2022)
This chapter concentrates on institutional differences in France and Germany. The stability of the German institutional setting contrasts with the series of institutional reforms that have stretched over decades or even half a century in France. While in Germany transformation has taken the form of successive adaptations, in France the diverse reforms have been hotly debated and sometimes even contested. Often the metropolises and regions form the focus of such discussions in France. These contrasts between stability and change can also be seen in both spatial planning systems and the position of the highest level of territorial authority (régions in France and Länder in Germany). Starting from the national policy guidelines in both countries, the authors describe different territorial units, their areas of responsibility and their manifold planning instruments. They also address processes of democratisation, participation and metropolisation, the role of the European Union and various crises as drivers of the development of both systems.
urn:nbn:de:0156-1119011; hdl:10419/266400; https://econpapers.repec.org/RePEc:zbw:arlfob:20
Keywords: 710; Policy guidelines; territorial units; planning instruments; drivers of change; role of EU